2006
DOI: 10.1038/sj.ejcn.1602532
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tolerance of erythritol and xylitol ingested in a liquid

Abstract: Objectives: To determine and compare the gastrointestinal (GI) responses of young adults following consumption of 45 g sucrose, 20, 35 and 50 g xylitol or erythritol given as a single oral, bolus dose in a liquid. Design: The study was a randomized, double-blind, placebo-controlled study. Subjects: Seventy healthy adult volunteers aged 18-24 years were recruited from the student population of the University of Salford. Sixty-four subjects completed the study. Interventions: Subjects consumed at home without su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 28 publications
1
67
0
Order By: Relevance
“…Occasionally noted temporary laxation and gastrointestinal discomfort [129,130] Not specified further metabolized to give energy in the amount of 2-2.4 calories per gram (Table 2). It was also found that lactitol is used as an energy source by special intestinal microflora in the colon, i.e., Bifidobacteria and Lactobacillus spp [47,48].…”
Section: Xylitolmentioning
confidence: 99%
“…Occasionally noted temporary laxation and gastrointestinal discomfort [129,130] Not specified further metabolized to give energy in the amount of 2-2.4 calories per gram (Table 2). It was also found that lactitol is used as an energy source by special intestinal microflora in the colon, i.e., Bifidobacteria and Lactobacillus spp [47,48].…”
Section: Xylitolmentioning
confidence: 99%
“…Erythritol had a high digestive tolerance and was noncaloric, non carcinogenic and non glycaemic and had antioxidant properties, it fits well into the functional food concepts to which it confers a healthy image (Storey et al 2007). …”
Section: Selection and Study Of Best Level Of Polyolsmentioning
confidence: 80%
“…Sorbitol has an antioxidizing effect and prevents fatty foods from turning rancid. Therefore, incorporation of polyols could be very useful to improve the texture and prolong the shelf life without staling (Storey et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, erythritol is better tolerated than xylitol, provoking less gastrointestinal side effects such as diarrhea and bloating. However, when erythritol is consumed as a single oral bolus exceeding 35 g, undesirable effects, including nausea and borborygmi, are common (18,19,25,37). Repetitive exposure appears to lead to increased tolerance through adaptive processes (23).…”
Section: Discussionmentioning
confidence: 99%